FAKTOR LUAS LAHAN, TENAGA KERJA, PUPUK DAN PENGALAMAN KERJA TERHADAP PRODUKSI KOPI GREEN BEAN DI KABUPATEN ACEH TENGAH - Ramadhan, Masri Ramadhan Masri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UGP, 2018)
The purpose of this research is to identify the factors of land, labor, fertilizer and work experience to the production of Green Coffee Bean in the village of Arul kumar Silih Nara District of Central Aceh district. The data used are primary data obtained through interviews direct from the growers, with a total sample of 38 farmers. The model used is Coob-Douglas function with OLS (Ordinary Least Square). The results of the estimate showed R2 value of 0.898. While the factors of land, labor, fertilizer use and experience of working with values ​​respectively 0.627; 0.319; 0.283; 0,033 positive and significant impact on coffee production to the level of significance value is smaller than the real tarap 0.01. While the analysis of Return to Scale (RTS) in getting the results 1262> 1; indicates when the input production increased by 1%, the production will increase in proportion to 1,262.